(untitled) (Revista UTCiencia: i-ISSN: 1390-6909. e-ISSN: 2602-8263, 2025)
Financial information plays a fundamental role in companies, enabling managers to make informed decisions. This information is essential to evaluate the economic situation of an entity, since it provides a clear and timely vision that facilitates strategic decisions based on reliable data, International Accounting Standards (IAS) provide guidelines for organizations to present financial statements in a consistent manner. In this regard, this conceptual research studies the incidence of IAS 16 on financial information, analyzing its importance, its impact on SMEs organizations and its relevance in the Ecuadorian context. This research used hermeneutics and phenomenology to obtain results. The theoretical methods were theoretical, deductive, and analytical-synthetic.